Use of Antenatal Steroids Treatment to Reduce Neonatal Respiratory Morbidity Prior to Cesarean Section in Preterm Birth - Ammar Noor, Wajeeha Rafi, Hafiz Muhammad Hashim Khan, Tayyab Arif Butt, Muhammad Inam Ul Haq, Muhammad Mohsin Bajwa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the rate of neonatal respiratory morbidity between individuals who received prenatal corticosteroids before to caesarean delivery at 34-37 weeks and those who did not. Patients and Methods: A total of 150 patients who presented with preterm labour having gestational age between 34-37 weeks and no neonatal congenital anomaly on anomaly scan were recruited from June-2021 to December-2021 from the gynecology unit of Nishtar Hospital Multan. Women divided into two groups. Group A; in these patients intramuscular dexamethasone (12 mg) was given in 2 doses 12 hours apart. Group B (Control group): in these patients no drug was given as a prophylaxis again neonatal respiratory morbidity. After delivery, each neonate was monitored for 24 hours after delivery to determine the respiratory morbidity. Results: Mean age of patients was 31.19±5.02 years. Mean gestational age was 35.66±1.10 weeks with range of 34-37 weeks. There were 78 (52.0%) patients who were prima-gravida and remaining 72 (48.0%) were Multi-gravida. There were 14 (9.3%) patients who were having previous abortion history. Respiratory morbidity was diagnosed in only 2 (2.7%) neonates in group A and in 07 (9.3%) neonates in group B (p-value 0.08) Conclusion: Prenatal corticosteroid therapy prior to elective caesarean section at 34–37 weeks of gestation significantly reduces neonatal respiratory morbidity.